Application of Matrix Converter to Wind Power Generation System - Juntham, C.; Tammaruckwattana, S. (My University, 2024)
This paper presents the application of a threephase matrix converter for wind power generation based on a permanent magnet synchronous generator (PMSG). The topology applied in the research is the 3 × 3 - matrix topology consisting of nine bi-directional switches. This paper focuses on the simulation of the proposed system using the MATLAB/ Simulink program to design the control algorithm for the PMSG. The algorithm and switching strategies acquired from the simulation will then be implemented on the real system using FPGA as the processor.
Keywords: Bi-Direction Switch; Commutation method; Matrix converter; Simulation; Switching loss